How do I change y-2x=7 into slope intercept form, and into standard form??

5 Answers | Add Yours

baxthum8's profile pic

baxthum8 | High School Teacher | (Level 3) Associate Educator

Posted on

Write the equation, `y - 2x = 7` into slope-intercept form and standard form.

To change to slope intercept form: `y = mx+b.`

Add 2x to both sides to isolate y.

`y-2x+2x = 7 + 2x`

` ``y = 2x+7`

`y-2x = 7` in slope-intercept form is `y = 2x+7` .

Standard Form: the standard form of a line is in the form Ax + By = C where A is a positive integer, and B, and C are integers.

`y-2x =7` Multiply every term by -1 to have x-coefficient positive.

`-1(y -2x)=7 rArr -y + 2x = -7`

Rearrange in `ax+by = c` form

`2x - y = -7`

` ``y-2x=7` in standard form is `2x-y=-7` .

ishpiro's profile pic

ishpiro | College Teacher | (Level 1) Educator

Posted on

Slope-intercept form of a linear equation looks as y = mx + b, where m is the slope and b is the y-intercept.

To change the equation y- 2x = 7 into slope-intercept form, isolate y by adding 2x to both sides:

y = 2x +7

Here, m = 2 is the slope and b = 7 is the y-intercept.

In standard form, a linear equation looks as ax + by = c, where a, b, and c are integers.

The given equation is already almost in standard form. All is needed is to exchange the order of the variables:

-2x + y = 7

One can also multiply both sides of the equation by - 1:

2x - y = -7

Answer: 

y = 2x + 7 (slope-intercept form)

2x - y = -7 (standard form)

acompanioninthetardis's profile pic

acompanioninthetardis | Student, Undergraduate | (Level 1) Valedictorian

Posted on

y-2x=7

simply add 2x to both sides to get slope intercept form

y= 2x+7

is slope intercept form which is the same as y=mx+b to get this 

whereas 

 standard form : 2x-y-7

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

y-2x=7  slope intercept form= y = mx + b     standard form= ax + by = c

to get the slope intercept form just add 2x to both sides you will end up with

y=2x+7

to get the standard form just minus 7 on both sides

y-7=2x  and minus y

-7=2x-y   just flip it

2x-y=-7 and voila!

We’ve answered 318,983 questions. We can answer yours, too.

Ask a question